2006
DOI: 10.1111/j.1365-3040.2005.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Can improvement in photosynthesis increase crop yields?

Abstract: The yield potential ( Y p ) of a grain crop is the seed mass per unit ground area obtained under optimum growing conditions without weeds, pests and diseases. It is determined by the product of the available light energy and by the genetically determined properties: efficiency of light capture ( e i ), the efficiency of conversion of the intercepted light into biomass ( e c ) and the proportion of biomass partitioned into grain ( h ). Plant breeding brings h and e i close to their theoretical maxima, leaving e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
981
5
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,316 publications
(1,070 citation statements)
references
References 94 publications
(196 reference statements)
24
981
5
14
Order By: Relevance
“…They can also result from changes in their metabolism of subtype C 4 photosynthesis (Ripley et al 2010). The findings of our study confirmed those of Hall (2003) and Long et al (2006), who warned that the cultivation of energy crops can adversely affect both the level of soil moisture and soil water storage, especially in the deeper layers. A clear reduction in moisture and soil water storage under cultures of HPP, together with its lowest E among all studied energy crop groups, is associated with a high area of leaves (usually equal to a critical or above LAI, providing 95% absorption PAR by the canopy), the total transpiration of which causes increases in both the water uptake and the evaporation of soil water.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…They can also result from changes in their metabolism of subtype C 4 photosynthesis (Ripley et al 2010). The findings of our study confirmed those of Hall (2003) and Long et al (2006), who warned that the cultivation of energy crops can adversely affect both the level of soil moisture and soil water storage, especially in the deeper layers. A clear reduction in moisture and soil water storage under cultures of HPP, together with its lowest E among all studied energy crop groups, is associated with a high area of leaves (usually equal to a critical or above LAI, providing 95% absorption PAR by the canopy), the total transpiration of which causes increases in both the water uptake and the evaporation of soil water.…”
Section: Discussionsupporting
confidence: 80%
“…Nearly the same phenomenon occurred in our studies. The use of instantaneous WUE in the performance assessment of various crops is complicated due to the leaf PN, which is poorly correlated with the yield when the different genotypes of a crop species are compared (Long et al 2006). This is a result of the increased g s and E in C 4 G.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the CO 2 concentration inside the leaf induces increases in photosynthetic efficiency, primarily by inhibiting the rubisco enzyme oxygenase activity (ribulose-1, 5-bisphosphate carboxylase/oxygenase) (Long et al 2006). Both biotypes showed a reduction in CE, especially from the third DAH ( Figure 1); until 7 DAH, the susceptible biotype presented significantly lower CE compared to the resistant biotype.…”
Section: Resultsmentioning
confidence: 98%
“…Receiving non-optimal levels of radiation reduces the efficiency of photosynthesis further; therefore, only 3 to 6 % of total solar radiation may be used in photosynthesis [11,12]. Ways to increase the photosynthetic efficiency of the plants is being actively researched to improve their yields, including those of the grain crops [13]. The pollutants such as sulfur dioxide and herbicides (weed killers) inhibit the photosynthesis [14,15].…”
Section: Introductionmentioning
confidence: 99%